Transforming Boring Grammar Teaching Methods into Fun Ones - Sugiyono Sugiyono (Lembaga Pengembangan Kinerja Dosen, 2025)
Grammar learning is often considered boring and less interesting by students because the presentation is monotonous and oriented towards memorization. This has an impact on low motivation and student learning outcomes in understanding grammar. An approach is needed that can change the way grammar material is delivered to be more fun and contextual. This study aims to measure the effectiveness of a fun grammar teaching method in improving student learning outcomes and motivation. The study also aims to identify students' perceptions of the learning approach. The study used a quasi-experimental design with two groups, namely the experimental and control, each consisting of 30 students. Data were collected through pre-test, post-test, and student perception questionnaires, and analyzed using SPSS. The experimental group showed a statistically significant increase in grammar learning outcomes compared to the control group. The questionnaire showed that students felt happier, more active, and more motivated in learning grammar with a fun method. The results of the correlation test also showed a strong relationship between students' positive perceptions and increased learning outcomes. The fun grammar teaching method has been proven to be effective in improving student learning outcomes and forming positive learning attitudes. This study offers an innovative approach to grammar teaching based on students' experiences, activities, and emotional involvement.